Percent Bed occupancy rate in a selected specialized tertiary care hospital in Dhaka city - Rahman, H; Haque, SME; Hafiz, MA (Bangladesh Journal of Medical Science, 2012)
Background and Aims: Providing a necessary care for a sick person outside home 'in hospes or hospital' dates back to nearly 300 century BC. In the present day hospital care facilities has been taken an institutional shape both in public and private sector. A hospital bed is both a scarce and expensive commodity in healthcare. Administrators running hospitals are in a dire need of objective measures and methods for efficient management of their limited financial resources. Bed utilization rates can be of immense help in realistic and effective decision making. The present study was undertaken to explore utilization of bed in a specialized tertiary care hospital in the Dhaka city. Methods: Hospital records of the year were reviewed- age, gender, disease profile, duration of hospital stay, outcome of treatment were recorded and bed occupancy rate was calculated. Data were presented as number, percentage and/ or mean SD, as appropriate. The dada were managed by Statistical Package for Social Science (SPSS) for Windows Version 10. Results: The results showed in the year 2001 total number of admissions were 13,305 of which 9953 (74.8%) were male and 3352 (25.2%) female. Average monthly admission was 1109. Maximum number of admissions (1304) was observed in the month of September of that year. Male admission rate was higher than female admission throughout the year. Among all the admission 27.2% were of road traffic accident cases. Among the admitted patients there was 57.3% discharge with advice, 1.9% death, 14.6% discharge on request bond, 12.7% discharge on request. Of all the admission there 12.5% found to be absconded. Bed occupancy rate was 79.75% and average length of stay in the hospital 18.47 days. Conclusions: The present data suggest that (i) in terms of bed occupancy rate the NITOR found to run in optimal capacity which, however, might be attributed to the relative high rate of ascendance and discharges on requests; (ii) average length of stay of patients appeared to be relatively longer and (iii) the management need to look into the issue and take appropriate measures to reduce patients unwanted long duration of stay and make the tertiary care hospital improve the quality of services. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9817 BJMS 2012; 11(1): 18-24